2018
DOI: 10.1371/journal.pone.0194953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical interaction between oleic acid and L-Arginine on oral perception, as a function of polymorphisms of CD36 and OBPIIa and genetic ability to taste 6-n-propylthiouracil

Abstract: Oral sensitivity to fats varies in individuals influencing nutritional status and health. Variations in oleic acid perception are associated with CD36 and odorant binding protein (OBPIIa) polymorphisms, and 6-n-propylthiouracil (PROP) sensitivity, which is mediated by TAS2R38 receptor. L-Arginine (L-Arg) supplementation was shown to modify the perception of the five taste qualities. Here we analyzed the effect of three concentrations (5, 10, 15 mmol/L) of L-Arg on oral perception of oleic acid in forty-six sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 115 publications
1
18
0
Order By: Relevance
“…There are a variety of variations in genes associated with a high or low incidence of tooth decay (Piekoszewska-Ziętek et al, 2017); Thus, Dental caries is a multi-factorial disease and cannot be limited to only one factor or gene (Weber, 2016). The current study, although not confirm this relation in this sample, suggests that the presence or compatibility of a number of environmental and genetic factors may shape this association, including a variety of genes, for example, it was found that the heterozygote genotypes of TAS2R38 gene were associated with certain genetic patterns of CA6-encoded carbonic anhydrase 6; an enzyme important in regulating pH capacity of saliva, which in turn affects the degree of tooth consistency and non-erosion when saliva buffer capacity is low (Li et al, 2015;Melis et al, 2018;Esberg et al, 2019) So, the genetic makeup of an individual from many genes and differences in expression of these genes may affect this relation or explain it.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…There are a variety of variations in genes associated with a high or low incidence of tooth decay (Piekoszewska-Ziętek et al, 2017); Thus, Dental caries is a multi-factorial disease and cannot be limited to only one factor or gene (Weber, 2016). The current study, although not confirm this relation in this sample, suggests that the presence or compatibility of a number of environmental and genetic factors may shape this association, including a variety of genes, for example, it was found that the heterozygote genotypes of TAS2R38 gene were associated with certain genetic patterns of CA6-encoded carbonic anhydrase 6; an enzyme important in regulating pH capacity of saliva, which in turn affects the degree of tooth consistency and non-erosion when saliva buffer capacity is low (Li et al, 2015;Melis et al, 2018;Esberg et al, 2019) So, the genetic makeup of an individual from many genes and differences in expression of these genes may affect this relation or explain it.…”
Section: Discussionmentioning
confidence: 52%
“…These studies included all the consensus of what has been proven impact. In addition, the appearance of the two phenotypes of PTC taste may be due to the involvement of other genes, not only the appearance of the PTC gene, including CA6 gene (Yildiz et al, 2016;Melis et al, 2018), which in turn affects the pH capacity of the saliva, a factor associated with tooth decay (Esberg et al, 2019). Due to the multifactorial nature of dental caries, the individual's vulnerability may differ from one another where some may be more susceptible to a higher risk of developing the disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fragments including the rs1761667 (G/A) SNP of CD36 were digested by the restriction enzyme (HhaI) according to Banerjee et al 2010 [77]. These methods have been validated by numerous studies [26,27,39,65,67,71,78]. Electrophoresis on a 2% agarose gel was used to separate the products of digestion.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Arginine L-arginine, when reacted with the enzyme called nitrous oxide synthase, produces a compound known as nitrous oxide. This compound has beneficial effects on lung physiology and cardiovascular functions [64]. Therefore, supplementing arginine in diet could be beneficial in combating COVID-19.…”
Section: Importance Of Dietary Supplementsmentioning
confidence: 99%